Therapeutic Effects Of Extracellular Vesicles From Human Menstrual Blood-derived Mesenchymal Stem Cells In Acute Lung Injury Animal Model - Lian, Jie (2023)
Human menstrual blood-derived mesenchymal stem cells (MenSCs) have gained attention for their therapeutic potential in various conditions. However, their specific application and mechanism in treating Acute lung injury (ALI) is still being explored. The aim of this study was to assess the effectiveness and potential underlying mechanisms of MenSCs derived-extracellular vesicles (EVs) in ameliorating acute lung inflammation and injury in preclinical models. Initially, MenSCs or their EVs were obtained and administered intratracheally to a mouse model with ALI induced by lipopolysaccharide (LPS) in order to assess their protective effects against pulmonary inflammation and injury. This evaluation was performed using histological, molecular, bronchoalveolar lavage fluid (BALF), and mRNA-sequencing analyses, taking into account the optimal timing for intervention. Subsequently, a small RNA microarray technique was employed to identify potential microRNAs (miRNAs) that contribute to the improvement of pulmonary inflammation and injury mediated by MenSC-EVs in vivo. Additionally, the intrinsic capacity of these potential miRNAs or their target genes in regulating lung inflammation and injury was examined both in vivo and in vitro by depleting them using an adeno-associated virus (AAV) and lentivirus-mediated technique, respectively. Furthermore, conventional molecular and biochemical experiments were conducted to elucidate the underlying molecular mechanism